Paper-Based Devices for Capturing Exosomes and Exosomal Nucleic Acids From Biological Samples - Lai, Chi-Hung; Lee, Chih-Ling; Vu, Cao-An; Vu, Van-Truc; Tsai, Yao-Hung; Chen, Wen-Yih; Cheng, Chao-Min (Frontiers in Bioengineering and Biotechnology, 2022)
Exosomes, nanovesicles derived from cells, contain a variety of biomolecules that can be considered biomarkers for disease diagnosis, including microRNAs (miRNAs). Given knowledge and demand, inexpensive, robust, and easy-to-use tools that are compatible with downstream nucleic acid detection should be developed to replace traditional methodologies for point-of-care testing (POCT) applications. This study deploys a paper-based extraction kit for exosome and exosomal miRNA analytical system with some quantifying methods to serve as an easy sample preparation for a possible POCT process. Exosomes concentrated from HCT116 cell cultures were arrested on paper-based immunoaffinity devices, which were produced by immobilizing anti-CD63 antibodies on Whatman filter paper, before being subjected to paper-based silica devices for nucleic acids to be trapped by silica nanoparticles adsorbed onto Whatman filter paper. Concentrations of captured exosomes were quantified by enzyme-linked immunosorbent assay (ELISA), demonstrating that paper-based immunoaffinity devices succeeded in capturing and determining exosome levels from cells cultured in both neutral and acidic microenvironments, whereas microRNA 21 (miR-21), a biomarker for various types of cancers and among the nucleic acids absorbed onto the silica devices, was determined by reverse transcription quantitative polymerase chain reaction (RT-qPCR) to prove that paper-based silica devices were capable of trapping exosomal nucleic acids. The developed paper-based kit and the devised procedure was successfully exploited to isolate exosomes and exosomal nucleic acids from different biological samples (platelet-poor plasma and lesion fluid) as clinical applications.